Existential distress in cancer: Alleviating suffering from fundamental loss and change - Vehling, Sigrun; Kissane, David W. (Psycho-oncology (Chichester, England), 2018)
A severe life threatening illness can challenge fundamental expectations about security, interrelatedness with others, justness, controllability, certainty, and hope for a long and fruitful life. That distress and suffering but also growth and mastery may arise from confrontation with an existentially threatening stressor is a long‐standing idea. But only recently have researchers studied existential distress more rigorously and begun to identify its distinct impact on health care outcomes. Operationalizations of existential distress have included fear of cancer recurrence, death anxiety, demoralization, hopelessness, dignity‐related distress, and the desire for hastened death. These focus in varying emphasis on fear of death, concern about autonomy, suffering, or being a burden to others; a sense of profound loneliness, pointlessness or hopelessness; grief, regret, or embitterment about what has been missed in life; and shame if dignity is lost or expectations about coping are not met. We provide an overview of conceptual issues, diagnostic approaches, and treatments to alleviate existential distress. Although the two meta‐analyses featured in this special issue indicate the progress that has been made, many questions remain unresolved. We suggest how the field may move forward through defining a threshold for clinically significant existential distress, investigating its comorbidity with other psychiatric conditions, and inquiring into adjustment processes and mechanisms underlying change in existential interventions. We hope that this special issue may inspire progress in this promising area of research to improve recognition and management of a central psychological state in cancer care.